2003
DOI: 10.1029/2002jd002997
|View full text |Cite
|
Sign up to set email alerts
|

Organic nitrogen in rain and aerosol in the eastern Mediterranean atmosphere: An association with atmospheric dust

Abstract: From March through early May of 2000, rain and bulk aerosol samples were collected at a coastal site on the eastern Mediterranean Sea at Erdemli, Turkey, and analyzed for nitrogen (N) species, including nitrate (NO3−), nitrite (NO2−), ammonium (NH4+), water‐soluble organic N, urea, and dissolved free amino acids. Other ions were also analyzed, including Ca2+, Mg2+, K+, Na+, Cl−, and SO42−. Water‐soluble organic N was found to contribute ∼17% and ∼26% of the total water‐soluble N in rain and aerosols, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 26 publications
16
101
2
1
Order By: Relevance
“…The maximum concentration of WSON was estimated to be 79 nmol N m −3 , with a mean value and standard deviation of 23.8 ± 16.3 nmol N m −3 . The observed arithmetic was comparable to that reported by Mace et al (2003a) for the same site. Approximately 66 % of the WSON was associated with coarse particles; the remaining fraction (34 %) was present within the fine mode.…”
Section: Positive Matrix Factorization (Pmf) For Source Apportionmentsupporting
confidence: 78%
See 4 more Smart Citations
“…The maximum concentration of WSON was estimated to be 79 nmol N m −3 , with a mean value and standard deviation of 23.8 ± 16.3 nmol N m −3 . The observed arithmetic was comparable to that reported by Mace et al (2003a) for the same site. Approximately 66 % of the WSON was associated with coarse particles; the remaining fraction (34 %) was present within the fine mode.…”
Section: Positive Matrix Factorization (Pmf) For Source Apportionmentsupporting
confidence: 78%
“…Percent contributions of coarse WSON for dust and non-dust events were almost identical, being 58 and 60 %, respectively. A similar enrichment of WSON during dust events has been reported for Erdemli (Mace et al, 2003a), the Yellow Sea (Shi et al, 2010) and Finokalia . In addition, Griffin et al (2007) have demonstrated a significant difference between dust and non-dust events for bacterial-and fungalcolony-forming units at Erdemli, the former being much greater.…”
Section: Influence Of Mineral Dust Episodes On Wson Aerosol Concentrasupporting
confidence: 52%
See 3 more Smart Citations